Evaluasi Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 2019 Pada Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Provinsi Kepulauan Riau - Liza Safitri; Rizki Romdoni, Mochammad; Salsa, Yulia (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2024)
Information technology which is developing rapidly at this time greatly influences the company's business conditions so that information technology governance is needed. COBIT 2019 is an information technology governance framework that has standards for implementing information technology governance. The Regional Office of the Ministry of Law and Human Rights, Riau Islands Province, is a government company that operates in the field of legal and human rights services. The aim of this research is to determine the current level of IT process capability (as-is) and the expected level of IT process capability (to-be) as well as providing recommendations and suggestions on better IT governance for the Regional Office of the Ministry of Law and Human Rights, Riau Islands Province. This research was conducted using standards framework COBIT 2019. From the existing process objectives, 8 objectives were obtained that were in accordance with the research, namely APO04 – Managed Innovation, APO07 – Managed Human Resources, APO13 – Managed Security, BAI02 – Managed Requirements Definitions, BAI03 – Managed Solutions Identification and Build, DSS03 – Managed Problems, DSS05 – Managed Security Services, MEA01 – Managed Performance and Conformance Monitoring, EDM01 – Ensured Governance Framework Setting and Maintenance. The results of this research show that the APO04 and EDM01 process objectives are at the capability level level 4 (as-is) with a capability value of APO04 and EDM01 of 100%, for DSS03 and MEA01 it is at the capability level level 5 (as-is) with a DSS03 and MEA01 capability value of 100%, for APO07 and APO13 it is at the capability level level 2 (as-is), and for domains BAI03 and DSS05 are at the capability level level 1 (as-is).